THE EFFECT OF DIGITAL ISLAMIC FINANCIAL INTEGRATION AND SHARIA COMPLIANCE ON THE DECISION TO CHOOSE TRAVEL MANARUL HUDA: THE ROLE OF CONSUMER TRUST - Sari Damayanti; Sri Dewi Anggadini (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to analyze the effect of perceived digital sharia finance integration and perceived compliance with sharia economic principles on the decision to use umrah travel services, with consumer trust as a mediating variable. Although digital transformation in umrah travel services is developing rapidly, research that simultaneously examines the role of digital sharia finance integration, compliance with sharia economic principles, and consumer trust in influencing service usage decisions remains limited. Therefore, this research is important to provide a more comprehensive understanding of the factors influencing consumer decisions in the sharia-based umrah travel industry. The research uses a quantitative approach with a survey method involving 150 pilgrims of Manarul Huda Travel, selected using a probability sampling technique with a random sampling approach. Data analysis was carried out using path analysis to test the direct and indirect effects among variables. The results show that perceived digital sharia finance integration and perceived compliance with sharia economic principles have a positive and significant effect on the decision to use umrah travel services, both directly and through consumer trust as a mediating variable. This finding confirms that strengthening the digital sharia financial service ecosystem, supported by consistent application of sharia economic principles, can increase consumer trust and encourage the decision to use the service. This research provides practical implications for umrah travel managers to strengthen a digital sharia financial service system that is transparent, secure, and in accordance with sharia principles as a strategy to increase trust and company competitiveness.